Methadone effects applied in the acupoint YinTang in female dog submitted to elective ovariohysterectomy: Case report - do Prado, Caroline (Pubvet, 2021)
The study was carried out in order to evaluate the sedative, analgesic effect and possible side effects of Methadone when applied in a sub-dose in the YinTang acupoint, located in the ventral midline between the eyebrows for an elective ovariohysterectomy. The sub-dose applied was 0.13 ml, and after twenty minutes, Xylazine was applied in a minimum dose, totaling 0.14 ml intramuscularly. To ensure the effectiveness of the drug, heart rate, respiratory rate, rectal temperature was measured every ten minutes during pre-anesthetic medication, totaling thirty minutes, and after the beginning of the surgery, the parameters were measured every fifteen minutes until completion. The degree of sedation the animal was in evaluated and painful stimuli were performed to determine the analgesia of animal, in addition to the observations of sialorrhea. After evaluating the collected data, it was found an effective sedation with a smaller amount of drugs because the reference values of hemodynamic standards remained constant throughout the procedure, so this technique can be used safely in the routine of veterinarians, also reducing side effects such as bradycardia and thus avoiding complications during the operations.
Keywords: Analgesia; pharmacopuncture; sedation; underdose